STRATEGI PENINGKATAN KUALITAS KARYAWAN PADA PT.SAWIT KHATULISTIWA LESTARI PEDADANG ESTATE KETUNGAU HILIR KABUPATEN SINTANG - Ratnasari, Evy (Universitas Kapuas Sintang, 2024)
This study examines the strategies for improving the quality of employees at PT. SawitKhatulistiwa Lestari Pedadang Estate in Ketungau Hilir, Sintang Regency. The focus of this research is toidentify the strategies used to enhance the quality of employees at PT. Sawit Khatulistiwa Lestari PedadangEstate. The research employs a descriptive qualitative method. The subjects of this study include managers,general employees, and employees from the R&D (Resource and Development) department. Data collectiontechniques used in the study are interviews, observations, and documentation studies. The results of thisstudy indicate that the company motivates and ensures the well-being of employees as a means ofimproving employee quality. The management frequently conducts training to enhance employees' skills,not only in industrial activities but also in personal and self-development skills. Employee attendance isquite high, with employees arriving and leaving according to working hours and being able to performtasks according to their positions and responsibilities. However, challenges arise from frequent budgetshortages due to the fact that a large portion of PT. Sawit Khatulistiwa Lestari Pedadang Estate's land isstill non-productive and in maintenance, and the process of appointing permanent employees takes a longtime. Based on the conclusions above, several recommendations are suggested: Regular training foremployees at PT. Sawit Khatulistiwa Lestari Pedadang Estate is needed to improve employee quality. Todetermine job satisfaction as an effort to improve employee quality, periodic opinion surveys should beconducted. The company's financial management needs to be improved to ensure timely wage payments.The company should seek funds that can be fully invested in maintaining the non-productive portion of theland